Hubungan Pengetahuan, Sikap, dan Ketersediaan Sarana dan Prasarana terhadap Perilaku Pemilahan Sampah pada Pedagang di Pasar Agung Kota Depok - Rozni, Zahira Hananda Naila; Sulistyorini, Desy (Jurnal Kesehatan Lingkungan Mandiri, 2024)
The waste problem in Indonesia is exacerbated by people's awareness and their actions regarding healthy lifestyles and a clean, waste-free environment. Many people do not realize the importance of waste processing, but there are also many people who understand the importance of waste processing but do not carry out this behavior. The researcher's aim is to determine the relationship between knowledge, attitudes, and availability of facilities and infrastructure on waste sorting behavior among traders at Pasar Agung, Depok City in 2023. Quantitative research method with a cross-sectional research design. The population in this research is all traders at Pasar Agung Depok City. The sampling technique was carried out using probability sampling and 78 samples were obtained. The data used is primary data distributed through a questionnaire. The research results show a p value of 0.027 (p > 0.05), meaning that there is a relationship between knowledge and waste sorting behavior, there is a relationship between attitude and waste sorting behavior, p value 0.020 (p > 0.05), conclusion : and there is a relationship between the availability of facilities and infrastructure and behavior. waste sorting p value 0.046 (p > 0.05). Suggestions from researchers hope that traders can separate waste according to type (organic and non-organic). And it is also hoped that traders can choose packaging that is used for the long term rather than single-use packaging. Traders can also choose more environmentally friendly materials, think and reconsider before purchasing an item.